La motivación laboral en la industria lojana de especerías (ile) de Babahoyo - Zamora Atariguana, Lady Eloiza (2019)
In the following case study to be carried out, the problems that exist in the Lojana de Especerías Ile de Babahoyo Industry will be detailed, where the employees currently have a regular level of motivation, so they do not carry out their activities with enthusiasm, it is specified that the main objective of this study is to analyze the level of motivation in the workplace of employees working in different areas of the company, in order to meet this objective the study techniques were used, which were the interview and the survey, in the same way it is specified which is the subline of investigation that was used, which is Model of Administrative Management